2017
DOI: 10.1016/j.chb.2017.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Mood and learning in navigation-based serious games

Abstract: Games are played for entertainment and have the ability to stimulate a variety of moods during gameplay, including happiness. Serious or applied games are created and used to serve a purpose rather than purely for entertainment. The relationship between mood and task efficiency has been investigated in psychology with contrasting results, and it also appears that there is a relationship between mood and learning. Players' mood and learning efficiency as a consequence of playing two serious games involving navi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 30 publications
0
31
0
2
Order By: Relevance
“…Different from entertaining games, serious games are designed for an educational rather than an entertaining purpose [1]. Serious games are referred to as entertaining tools with a purpose of education, where players cultivate their knowledge and practice their skills through overcoming numerous hindrances during gaming.…”
Section: Introductionmentioning
confidence: 99%
“…Different from entertaining games, serious games are designed for an educational rather than an entertaining purpose [1]. Serious games are referred to as entertaining tools with a purpose of education, where players cultivate their knowledge and practice their skills through overcoming numerous hindrances during gaming.…”
Section: Introductionmentioning
confidence: 99%
“…The experience of the world shapes our emotional representation of it, and in turn, our emotional predisposition does not affect only our behaviour, but also our inclination towards the events in our life [3,4]. In a recent study, we found that emotions also influenced the amount of information people learned and the knowledge transferred from the training into the real world [5].…”
mentioning
confidence: 99%
“…The experience of the world shapes our emotional representation of it, and in turn, our emotional predisposition does not affect only our behaviour, but also our inclination towards the events in our life [3,4]. In a recent study, we found that emotions also influenced the amount of information people learned and the knowledge transferred from the training into the real world [5].McConnell and Eva extensively reviewed the literature on the influence of emotion in learning and the resulting transfer of skills and knowledge to the real world [6]. They concluded that emotion influences how learners identify, perceive, interpret information and act during training.…”
mentioning
confidence: 99%
See 2 more Smart Citations